2023
DOI: 10.3390/nu15183885
|View full text |Cite
|
Sign up to set email alerts
|

Stand Up to Stand Out: Natural Dietary Polyphenols Curcumin, Resveratrol, and Gossypol as Potential Therapeutic Candidates against Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Zhonglei Wang,
Xian-qing Song,
Wenjing Xu
et al.

Abstract: The COVID-19 pandemic has stimulated collaborative drug discovery efforts in academia and the industry with the aim of developing therapies and vaccines that target SARS-CoV-2. Several novel therapies have been approved and deployed in the last three years. However, their clinical application has revealed limitations due to the rapid emergence of viral variants. Therefore, the development of next-generation SARS-CoV-2 therapeutic agents with a high potency and safety profile remains a high priority for global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 164 publications
0
3
0
Order By: Relevance
“…Polyphenols are a group of naturally occurring compounds found in various plantbased foods, such as fruits, vegetables, whole grains, and beverages like tea and red wine [1]. They have gained considerable attention for their potential health benefits and their ability to counteract cancer onset and progression [2].…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are a group of naturally occurring compounds found in various plantbased foods, such as fruits, vegetables, whole grains, and beverages like tea and red wine [1]. They have gained considerable attention for their potential health benefits and their ability to counteract cancer onset and progression [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a human study in Pakistan evaluated the efficacy and safety of an oral curcumin-quercetin supplement plus standard care vs. standard care alone in outpatients with early-stage COVID-19. The study found that the curcumin-quercetin group had a significantly higher viral clearance (18/25 (72.%)) compared to that of the control group [266]. In addition, curcumin-quercetin reduced acute COVID-19 symptoms in a group compared to a control group [266].…”
Section: Curcuminmentioning
confidence: 91%
“…The study found that the curcumin-quercetin group had a significantly higher viral clearance (18/25 (72.%)) compared to that of the control group [266]. In addition, curcumin-quercetin reduced acute COVID-19 symptoms in a group compared to a control group [266].…”
Section: Curcuminmentioning
confidence: 91%